2009
DOI: 10.1007/s00134-009-1611-4
|View full text |Cite
|
Sign up to set email alerts
|

Family satisfaction in the intensive care unit: what makes the difference?

Abstract: Purpose: To assess family satisfaction in the ICU and to identify parameters for improvement. Methods: Multicenter study in Swiss ICUs. Families were given a questionnaire covering overall satisfaction, satisfaction with care and satisfaction with information/decision-making. Demographic, medical and institutional data were gathered from patients, visitors and ICUs. Results: A total of 996 questionnaires from family members were analyzed. Individual questions were assessed, and summary measures (range 0-100) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
143
3
17

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(171 citation statements)
references
References 40 publications
8
143
3
17
Order By: Relevance
“…Stricker et al 55 (in a multicentre evaluation of factors associated with family satisfaction using the German version of the FS-ICU-34 but scored using the 24 items of the FS-ICU-24) found that, among 996 family members of both ICU survivors and non-survivors in 23 ICUs, increasing acute severity of illness of the patient [evaluated using the Simplified Acute Physiology Score (SAPS) II] was associated with increasing satisfaction on the overall family satisfaction score, and lower satisfaction was associated with ICU-level characteristics of a written admission/discharge policy and a higher patient-nurse ratio. Family member characteristics of sex and relationship to the patient were included in the multivariable model but not found to be significantly associated with satisfaction.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Stricker et al 55 (in a multicentre evaluation of factors associated with family satisfaction using the German version of the FS-ICU-34 but scored using the 24 items of the FS-ICU-24) found that, among 996 family members of both ICU survivors and non-survivors in 23 ICUs, increasing acute severity of illness of the patient [evaluated using the Simplified Acute Physiology Score (SAPS) II] was associated with increasing satisfaction on the overall family satisfaction score, and lower satisfaction was associated with ICU-level characteristics of a written admission/discharge policy and a higher patient-nurse ratio. Family member characteristics of sex and relationship to the patient were included in the multivariable model but not found to be significantly associated with satisfaction.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Of the 21 studies, 16 were based on single publications from a single cohort 17,[38][39][40][41][42][55][56][57][72][73][74][75][78][79][80] and five were based on multiple publications from overlapping cohorts. 9,10,53,54,[59][60][61][62][63][64][65][66][67][68][69][70][71]76,77 These studies are reported between 2002 and 2014.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical expressions of association cannot do justice to the complexity of negotiating consensus with and amongst families who are engaged in end-of-life decision-making. Certainly Stricker and colleagues were limited by what they could measure in this quantitative study [4]. There are probably many more pertinent issues that were not investigated, some of which are not measurable quantitatively.…”
mentioning
confidence: 96%
“…In this issue of Intensive Care Medicine, Stricker and colleagues used the FS-ICU 24 to further contribute to what is known about family satisfaction in the ICU [4]. In 2007, they distributed 1,321 questionnaires at 23 adult Swiss-German ICUs and provide here an analysis of the 996 completed questionnaires (response rate 75%).…”
mentioning
confidence: 99%